Recent Advances in Energy Harvesting Technologies - Rajput, Shailendra (River Publishers, 2023)
This book discusses the application of artificial intelligence (AI) for energy harvesting
Description based on publisher supplied metadata and other sources
Keywords: Power resources; Electric power production; Energy harvesting